Analisis Kelayakan Bisnis Ditinjau dari Aspek Pasar, Aspek Pemasaran dan Aspek Keuangan pada UMKM Makanan Khas Bangka di Kota Pangkalpinang - Dony Yanuar (JURNAL EKOMBIS, 2018)
Abstract: This study analyzes the aspects of market, marketing, and finance of the small business of traditional snack industries. Analysis on these aspects is required in order to determine the feasibility of business development of small business of traditional Bangka snack industries.This study uses quantitative and qualitative analysis to analyze aspects of market, marketing and finance. For the market aspects, there are analyses of demand, supply and market forms. For the marketing aspects, there are analyses of market segmentation, target market, market positioning, SWOT analysis, competitor and marketing mix, while for the financial aspect there are analyses of Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, Profitabilty Index (PI) .Keywords: Bangka snack indsutries, Aspect of Market, Marketing and Finance.